Strategic dimension for theory of constraints and its impact in decision making: بحث تطبيقي في الشركة العامة للصناعات الجلدية (Journal of Accounting and Financial Studies ( JAFS ), 2013)
The research illustrated that the theory of constraints is   "A group of concepts and basics that aim at helping the management in order to determine the difficulties and how to overcome these difficulties through determining the necessary change and how these change can be done efficiently and effectively ".       The research showed that the theory of constraint including its tools calls for magnifying throughput, constricting the product cycle , determining  the optimal production mix , utilization of scare resources and canceling the idle time , that achieving  throughput  increasing  then  increasing  profit .      Moreover, throughput accounting (one of the TOC tools) is a developed approach that links between the measurement of the achieved throughput during a specified period of time and the resources which used for achieving this throughput  through embodied in specifying the points of bottlenecks or the constraints that come through the operations during all stages in their capacity, this specification will lead to an essential  difference in the nature of the decisions that were built on these information .